Trace elements in maternal serum and their relationships with preterm birth and fetal growth restriction - Irwinda, Rima; Sungkar, Ali; Surya, Raymond; Guinto, Valerie Tiempo (UI Scholars Hub, 2020)
Background: Preterm birth (PTB) and fetal growth restriction (FGR) contribute to high hospital costs. An imbalance in the concentration of the four trace elements (i.e., copper, zinc, iron, and calcium) was shown to be associated with complications during pregnancy. This study aimed to analyze the role of these trace elements in the occurrence of PTB and FGR. Methods: A search was conducted in PubMed, Cochrane Library, and Ovid. The articles were filtered based on the inclusion and exclusion criteria, and further screening was based on the association of articles with the clinical question. The risk of bias in each of the studies was assessed using the Cochrane risk of bias table. Forrest plots were created and analyzed using Review Manager 5.3e. Results: Three studies were included in the risk of bias assessment and meta-analysis. Maternal serum levels of copper and iron were lower in the FGR group (p < 0.05), while copper, zinc, iron, and calcium were lower in the PTB group (p < 0.05). The included studies had a low degree of homogeneity (I2 < 50%). Conclusion: Maternal iron deficiency was associated with FGR, while low levels of the trace elements copper, zinc, iron, and calcium were associated with PTB.